Examining the role of joint visual attention and tactile artefacts in enhancing long-term memory - Saarnio, Janina (2024)
Daily routines in knowledge-driven work are built around meetings whose practices are not optimized. Relying mainly on verbal and textual exchange of information, misunderstandings can easily occur when the aim is to solve complex cause-and-effect relationships. This thesis study leveraged tactile artefacts as visual communication aids in strategy development. Visual communication methods are said to provide visual points of reference for individual mental models, which facilitate the building of common ground and shared understanding. Besides enhancing communication and strategy development, tactile artefacts were assumed to attract (joint) visual attention of the participants working in groups of 3-4 people, which was studied using mobile eye-tracking. Previous research has found that joint visual attention (JVA) enhances collaboration quality and learning. This thesis examined the effect of (joint) visual attention on visual and narrative long-term memory of the collaborative developed strategy, which was assessed with a half-structured online interview. The narrative long-term memory referred to the verbally explainable strategy, which was iteratively developed with the help of tactile artefacts, while the visual long-term memory pertained to individual artefacts and their assigned meanings. Additionally, the initiators of JVA events were examined from the eye-tracking data, as initating JVA has been shown to enhance recognition memory. The effect of JVA and initiating JVA on long-term memory was analysed with the binary logistic mixed-effects model, using gaze visit—defined as detected continuous gaze on the area-of-interest—as the unit of analysis. The sole effect of visual attention on long-term memory was analysed with a linear mixed-effects model with visit duration as a dependent variable. The results indicate that JVA does not enhance narrative or visual long-term memory. However, initiating JVA does enhance visual long-term memory. The eye-tracking metrics also revealed that the number of fixations during a visit increase the odds of both JVA and initiating JVA, whereas longer visit duration decrease the odds of both. The findings of this study highlight the importance of dynamic and proactive visual engagement and participation in enhancing long-term memory in collaborative settings.